Can transitioning to non-renewable modern energy decrease carbon dioxide emissions in India?. (September 2022) - Pascale, Andrew; Chakravarty, Shoibal; Lant, Paul; Smart, Simon; Greig, Chris
Abstract: Traditional discussions of the relationships between energy, carbon dioxide (CO2 ) emissions and human development fail to expose within country energy and CO2 emissions inequality. This work seeks to elucidate these inequalities in India and then investigate the consequential impacts on welfare and CO2 emissions of India's transition away from energy poverty. The study uses the India Human Development Survey and the EORA database to generate household Human Development Index scores, consumption and CO2 emissions distributions for India in both 2005 and 2012. Results suggest that addressing pressing welfare issues connected to energy use in India, such as indoor air pollution from solid fuels, can be aided by a transition to modern energy carriers, with little consequential increase in CO2 emissions. The richest 10 % of Indians only emitted 20 % more emissions from direct primary energy use than the poorest 10 % in 2012 (excluding direct emissions from transport). However, the wealth creation needed to sustain a modern energy transition will inevitably coincide with increased consumption, consumption which is supported by carbon intensive electricity and materials and represents the fastest growth area for CO2 emissions as incomes rise. The richest 10 % of Indians emitted five times more emissions from indirect energy use than the poorest 10 % in 2012. Addressing these challenges at the same time requires a coherent strategy that targets energy poverty and wealth creation in the poorest deciles, while reducing the emissions intensity of the sectors – notably transportation – of the Indian and global economies supporting increasing household consumption.